Real-time Value Creation Metrics in Manufacturing Through Blue Innovation and IoT-Based Accounting - Renaldo, Nicholas; Fransisca, Luciana; Junaedi, Achmad Tavip; Tanjung, Amries Rusli; Chandra, Teddy; Suharti, Suharti; Andi, Andi; Suhardjo, Suhardjo; Augustine, Yvonne; Musa, Sulaiman (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This study aims to explore the impact of Blue Innovation and IoT-based accounting on value creation in the manufacturing sector. Novelty on this research are integration of Blue Innovation and IoT-Based Accounting. Real-Time Value Creation Metrics introduces a framework for evaluating real-time financial and environmental impact through IoT-enabled accounting systems, providing a more dynamic approach compared to traditional static reporting methods. This research follows a qualitative exploratory approach to understand the intersection of Blue Innovation and IoT-based accounting in manufacturing. To ensure the novelty of this research, the following methodological steps are undertaken Comparative Gap Analysis, Conceptual Model Development, Validation Through Expert Panels, and Empirical Case Study Verification. The study provides empirical evidence that IoT-driven financial tracking improves both cost efficiency and sustainability compliance. Blue Innovation practices emphasize the integration of sustainable processes into core business operations. The development of Real-Time Value Creation Metrics (RTVCM) marks a significant contribution to modern accounting frameworks, offering a more dynamic and data-driven approach compared to traditional financial reporting. Future studies can expand the RTVCM framework by integrating AI-driven predictive analytics for sustainability reporting.